Evaluation of prednisolone and prednisolone sodium succinate concentrations in human plasma and inner ear perilymph during cochlear implantation 24 h after intratympanic injection. (2nd December 2022) - Covelli, Edoardo; Filippi, Chiara; Filipo, Roberto; Palumbo, Giancarlo; Di Giovanni, Carmen; Elfarargy, Haitham H.; Barbara, Maurizio
Abstract: Background: The use of intratympanic (IT) steroids has drastically increased over the past 10–15 years to manage many otological pathologies. Objectives: This study aimed to compare the concentrations of prednisolone and prednisolone sodium succinate (SS) in the plasma and inner ear perilymph of participants who underwent cochlear implantation 24 h after IT injection. Materials and methods: It was a prospective comparative randomized study. Twenty participants received an IT injection of prednisolone SS ∼24 h before the cochlear implantation. The other five participants received an IT saline injection and represented the control group. Perilymph and blood were sampled during the cochlear implantation surgery. Results: Both prednisolone and prednisolone SS were still present in perilymph ∼24 h after the IT administration. Only prednisolone was present in the blood plasma of seven participants (35%). Conclusion: IT injection of prednisolone SS resulted in high perilymph concentrations of prednisolone and prednisolone SS, which could stay in the perilymph for at least 24 h. Using a mini-endoscope during the IT injection may effectively detect barriers infront of the round window membrane, increasing the drug concentration in the inner ear. Significance: IT injection is an effective method for delivering prednisolone to the inner ear.